Development and Evaluation of an Enzyme Based Time Temperature Integrator (TTI) for Monitoring Meat Quality - Vishnuraj, M. R.; Kandeepan, G.; Shukla, Vivek; Kumar, Sanjay; Arvind; Singh, Bhanu Pratap; Bhattacharya, Dipanwita; Sharma, Hemant (Journal of Meat Science, 2016)
A colorimetric enzyme-substrate based time temperature integrator (TTI) with potential for the development of intelligent packing tool, as a quality monitoring system for fresh meat under temperature abuse, is described. This biological TTI, which contains enzyme α-amylase and substrates iodine and starch, can produce a visible colour change on exposure to Ã 10°C. A ready to use TTI preparation protocol was standardized with respect to substrate and enzyme combinations, drying temperature and quantity of water required. Various constant temperature (°C) regimes of 4±1, 25±1 and 37±1 was followed for standardization of frozen (-18±1°C) fabricated TTI’s. A colour response spanning from initial bluish black to final light yellow was observed on isothermal storage experiment. The rapid sequential colour response at 37±1°C compared to 25±1°C and unresponsiveness of TTI at 4±1°C explains temperature dependent kinetics of the present biological TTI. At last a colour chart was developed to compare the TTI’s colour response with fresh meat quality under various constant temperature abuse conditions.